Biomarkers of Glycocalyx Injury and Endothelial Activation are Associated with Clinical Outcomes in Patients with Sepsis: A Systematic Review and Meta-Analysis (2022)
Objective: Sepsis is one of the main causes of morbidity and mortality worldwide. Microcirculatory impairment, especially damage to the endothelium and glycocalyx, is often not assessed. The objective of this systematic review and meta-analysis was to summarize the available evidence of the risk of unsatisfactory outcomes in patients with sepsis and elevated glycocalyx injury and endothelial activation biomarkers. Design: A systematic search was carried out on PubMed/MEDLINE, Embase, Cochrane and Google Scholar up to December 31, 2021, including studies in adults and children with sepsis which measured glycocalyx injury and endothelial activation biomarkers within 48 hours of hospital admission. The primary outcome was the risk of mortality from all causes and the secondary outcomes were the risk of developing respiratory failure (RF) and multiple organ dysfunction syndrome (MODS) in patients with elevations of these biomarkers. Measurements and main results: A total of 17 studies (3,529 patients) were included: 11 evaluated syndecan-1 (n=2,397) and 6 endocan (n=1,132). Syndecan-1 was higher in the group of patients who died than in those who survived [255 ng/mL (IQR: 139-305) vs. 83 ng/mL (IQR:40-111); p=0.014]. Patients with elevated syndecan-1 had a greater risk of death (OR 2.32; 95% CI 1.89, 3.10: p<0.001), MODS (OR 3.3; 95% CI 1.51, 7.25: p=0.003;), or RF (OR 7.53; 95% CI 1.86-30.45: p=0.005). Endocan was higher in patients who died [3.1 ng/mL (IQR 2.3, 3.7) vs. 1.62 ng/mL (IQR 1.2, 5.7); OR 9.53; 95% CI 3.34, 27.3; p<0.001], who had MODS (OR 8.33; 95% CI 2.07, 33.58; p=0.003) and who had RF (OR 9.66; 95% CI 2.26, 43.95; p=0.002). Conclusion: Patients with sepsis and abnormal glycocalyx injury and endothelial activation biomarkers have a greater risk of developing respiratory failure, multiple organ failure, and death. Microcirculatory impairment should be routinely evaluated in patients with sepsis, using biomarkers to stratify risk groups. Keywords: endocan; endothelium; microcirculation; mortality; respiratory failure; septic shock; syndecan-1.